Impact evaluation of the “Paz y Justicia” programme to reduce homicides in Honduras - Rojido, Emiliano (International journal of comparative and applied criminal justice, 2022)
Paz y Justicia is an innovative programme in which a civil society organisation conducts criminal investigations of homicides in high-incidence communities of Tegucigalpa and San Pedro Sula, taking on a characteristic role of the State. The objective of this article is to understand how the programme works and to evaluate its impact. The evaluation design is based on control groups with similar homicide rates and socio-economic indicators as the intervened areas. Given the lack of reliable data to calculate indictment and conviction rates, the incidence of homicides is considered as the only dependent variable. Qualitative data were also gathered, through semi-structured interviews and field visits, in order to gain a deeper understanding of the programme. The impact evaluation reveals that Paz y Justicia can reduce homicides in the areas in which it operates, but this effect is not universal. The article discusses possible mechanisms to explain these results.